Fabrication and Characterization of Low-Cost Raw Coconut Husk and Activated Carbon Coconut Husk/Epoxy-3D Printed Honeycomb Structure as An Electromagnetic Wave : Absorbing Material - Raudhahtul Insyirah Miswan; Muadzam Fahmy Mokhtar; Fadzidah Mohd Idris (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology